Effects of Son Preference on Contraceptive Use in Bangladesh - Hoq, Mohammad Nazmul (Kesmas, 2019)
Son preference resulting from traditional beliefs, social customs and economic benefits including support of aging parents is widespread not only in Bangladesh but also in many Asian and African countries, which are believed for low levels of contraceptive use. To carry out the research task effectively and efficiently, the research work extracted 16,858 currently married women aged 15-49 out of 17,863 ever-married women from a nationally representative 2014 Bangladesh Demographic and Health Survey Data (BDHS, 2014) set. Levels of contraceptive prevalence rate of the respondents having only daughters is found only 48.4, which is remarkably lower than the national average (62.4) because of son preference. The analysis reveals that son preference is variant regarding of place of residence and socioeconomic background. Son preference is stronger among illiterate, nonworking women and women above 40 years of age. Moreover, Muslim women have a strong son preference than their Non-Muslim counterparts. The desire for sons can be reduced by making daughters and sons equally dear to parents and also in society.